The Decline in Private Saving Rates in the 1990s in OECD Countries How Much Can Be Explained by Non-wealth Determinants? - Pelgrin, Florian (OECD Publishing, 2003)
The substantial decline in private-sector saving rates observed in several OECD countries in the late 1990s coincided in several cases with a sharp increase in household financial net worth. This was seen by many observers as evidence that the strong rise in equity and residential property prices during the late 1990s had been treated by households as a permanent increase in wealth, leading to an unsustainable drop in saving and raising fears of an eventual negative wealth effect. Applying estimation techniques for systems of dynamic panel equations, this paper looks at basic determinants of private saving for a sample of 15 OECD countries and finds that the sharp decline in saving observed after 1995 can be largely explained, even in a post-sample fashion, by fundamentals other than financial wealth. Among the determinants, the rise in public-sector saving is found to have contributed the most to the decline in private saving between 1995 and 2000. Based on this investigation, there is little evidence that consumers had gone too far in responding to the stock market boom of the late 1990s, even in countries where private saving rates have fallen to historically low levels. On the other hand, the results suggest that a loosening of fiscal policy may have a limited stimulatory impact on private consumption...